Muslim views on organ transplant - Shuriye, Abdi Omar (IIUM Press, 2011)
In Islamic worldview human cadaver is considered holy and sacred as of the living person. The human dignity bestowed on all mankind applies and it is extended to the corpse. For this reason, in the Muslim world at least, organ transplant has been contentious process. This paper is a study on the procedures and ethical implications of organ transplant. It evaluates the Islamic views on the issue.